A framework for business transformation through enterprise-wide, automated, profit-maximised planning. (5th April 2010) - Santhanakrishnan, S.; SenGupta, Siddhartha; Narendran, T.T.
The ever-increasing scale and complexity of globalising enterprises is making business transformations riskier. We develop a framework for such initiatives building on a deeper understanding of an enterprise's drivers, structure, and interactions. It then amalgamates the structured approaches of enterprise architecture with business-aware methods of enterprise engineering to suggest directions the framework should adopt. We suggest that the framework supports integrated, automated and profit-optimised business planning as the essence of all transforms. We then deal with processes and management approach that the framework should support and share directions for further research focussed on various flows and their transformations through the enterprise.